Proactive and Preventive Student Welfare Activities in Finnish Preschool and Elementary School: Handling of Transition to Formal Schooling and a National Anti-Bullying Program as Examples - Ahtola, Annarilla (fi=Turun yliopisto|en=University of Turku|, 2012)
Prerequisites and effects of proactive and preventive psycho-social student welfare activities in Finnish preschool and elementary school were of interest in the present thesis. So far, Finnish student welfare work has mainly focused on interventions and individuals, and the voluminous possibilities to enhance well-being of all students as a part of everyday school work have not been fully exploited. Consequently, in this thesis three goals were set: (1) To present concrete examples of proactive and preventive psycho-social student welfare activities in Finnish basic education; (2) To investigate measurable positive effects of proactive and preventive activities; and (3) To investigate implementation of proactive and preventive activities in ecological contexts. Two prominent phenomena in preschool and elementary school years—transition to formal schooling and school bullying—were chosen as examples of critical situations that are appropriate targets for proactive and preventive psycho-social student welfare activities. Until lately, the procedures concerning both school transitions and school bullying have been rather problem-focused and reactive in nature. Theoretically, we lean on the bioecological model of development by Bronfenbrenner and Morris with concentric micro-, meso-, exo- and macrosystems. Data were drawn from two large-scale research projects, the longitudinal First Steps Study: Interactive Learning in the Child–Parent– Teacher Triangle, and the Evaluation Study of the National Antibullying Program KiVa. In Study I, we found that the academic skills of children from preschool–elementary school pairs that implemented several supportive activities during the preschool year developed more quickly from preschool to Grade 1 compared with the skills of children from pairs that used fewer practices. In Study II, we focused on possible effects of proactive and preventive actions on teachers and found that participation in the KiVa antibullying program influenced teachers‘ self-evaluated competence to tackle bullying. In Studies III and IV, we investigated factors that affect implementation rate of these proactive and preventive actions. In Study III, we found that principal‘s commitment and support for antibullying work has a clear-cut positive effect on implementation adherence of student lessons of the KiVa antibullying program. The more teachers experience support for and commitment to anti-bullying work from their principal, the more they report having covered KiVa student lessons and topics. In Study IV, we wanted to find out why some schools implement several useful and inexpensive transition practices, whereas other schools use only a few of them. We were interested in broadening the scope and looking at local-level (exosystem) qualities, and, in fact, the local-level activities and guidelines, along with teacherreported importance of the transition practices, were the only factors significantly associated with the implementation rate of transition practices between elementary schools and partner preschools. Teacher- and school-level factors available in this study turned out to be mostly not significant. To summarize, the results confirm that school-based promotion and prevention activities may have beneficial effects not only on students but also on teachers. Second, various top-down processes, such as engagement at the level of elementary school principals or local administration may enhance implementation of these beneficial activities. The main message is that when aiming to support the lives of children the primary focus should be on adults. In future, promotion of psychosocial well-being and the intrinsic value of inter- and intrapersonal skills need to be strengthened in the Finnish educational systems. Future research efforts in student welfare and school psychology, as well as focused training for psychologists in educational contexts, should be encouraged in the departments of psychology and education in Finnish universities. Moreover, a specific research centre for school health and well-being should be established.

Hyvinvointia edistävä ja ongelmia ennaltaehkäisevä oppilashuoltotyö esi- ja perusopetuksessa. Esimerkkeinä nivelvaiheen yhteistyö ja KiVa Koulu -toimenpideohjelma Tässä väitöskirjatyössä tutkittiin hyvinvointia edistävän ja ongelmia ennaltaehkäisevän oppilashuoltotyön vaikutuksia ja ennakkoehtoja suomalaisessa esi- ja perusopetuksessa. Lainsäädännön ja opetussuunnitelmien perusteiden linjauksista huolimatta esi- ja perusopetuksen oppilashuoltotyö on tähän saakka ollut melko yksilö- ja ongelmakeskeistä, ja mahdollisuutta edistää kaikkien koululaisten hyvää oppimista ja hyvinvointia osana koulun arkea ei ole hyödynnetty riittävästi. Tämän työn tavoitteina oli: (1) Tarjota konkreettisia esimerkkejä siitä, mitä hyvinvointia edistävä ja ongelmia ennaltaehkäisevä oppilashuoltotyö on. (2) Tutkia tämän työn mahdollisia myönteisiä vaikutuksia. (3) Tutkia hyvinvointia edistävän ja ongelmia ennaltaehkäisevän oppilashuoltotyön toteutumiseen vaikuttavia tekijöitä esi- ja perusopetuksen ekologisessa kontekstissa. Tutkittaviksi ilmiöiksi valittiin peruskoulun aloittaminen sekä koulukiusaaminen, joihin on aiemmin puututtu lähinnä ongelmakeskeisesti arvioimalla koulutulokkaiden kouluvalmiutta ja puuttumalla ilmenneisiin kiusaamistapauksiin. Koska koulun aloittaminen sekä toverisuhteet ja ryhmäilmiöt koskevat koko ikäluokkaa, hyödyllisempää olisi pohtia jo ennalta, miten niiden onnistumista voidaan tukea kaikkien lasten kohdalla. Tutkimuksen teoreettisena taustana on Bronfenbrennerin ja Morrisin bioekologinen kehitysteoria, joka perustuu sisäkkäisille konteksteille, mikro-, meso-, ekso- ja makrosysteemeille. Tutkimus on osa kahta mittavaa hanketta, Alkuportaat-pitkittäistutkimusta sekä KiVa Koulu, kiusaamisen vastainen toimenpideohjelma -vaikuttavuustutkimusta. Tutkimuksen ensimmäisessä osatyössä havaittiin, että kun esikoulu ja alkuopetus tekivät esikouluvuoden aikana runsaasti nivelvaiheyhteistyötä, oppilaiden akateemiset taidot kehittyivät 1. luokan aikana nopeammin. Toisessa osatyössä tutkittiin hyvinvointia edistävän ja ongelmia ennaltaehkäisevän työn vaikutuksia opettajiin ja havaittiin, että osallistuminen KiVa Koulu - ohjelmaan vaikutti opettajan itsearvioituihin valmiuksiin tarttua kiusaamiseen. Kolmas ja neljäs osatyö keskittyivät tarkastelemaan, mitkä tekijät vaikuttavat hyvinvointia edistävien ja ongelmia ennaltaehkäisevien toimenpiteiden toteutumiseen kouluissa. Kolmannessa osatyössä osoitimme, että rehtorin sitoutuminen KiVa Koulu -toimenpideohjelmaan vaikutti myönteisesti siihen, miten aktiivisesti opettajat pitivät ohjelmaan kuuluvia ennaltaehkäiseviä oppitunteja. Kun opettajat kokivat rehtorin olevan sitoutunut kiusaamisen vastaiseen työhön ja saavansa häneltä tukea, he pitivät enemmän oppitunteja ja käsittelivät tunneilla enemmän aiheita. Neljännessä osatyössä selvitimme, miksi kustannustehokasta nivelvaiheen yhteistyötä tehdään joissain kouluissa enemmän kuin muissa. Näkökulma oli erityisesti kuntatason toiminnassa, ja pystyimmekin osoittamaan, että kahden kunnan väliltä löytyi merkittävämpiä eroja kuin koulujen tai yksittäisten opettajien väliltä. Toisessa tutkimuskunnassa nivelvaiheen yhteistyön kehittämiseen oli systemaattisesti panostettu esiopetuksen ja perusopetuksen hallinnon tasolla. Myös yksittäisten opettajien arvio nivelvaiheyhteistyön tärkeydestä oli yhteydessä heidän ilmoittamaansa nivelvaiheyhteistyön määrään. Yhteenvetona voidaan todeta, että hyvinvointia edistävät ja ongelmia ennaltaehkäisevät toimet voivat olla hyödyllisiä paitsi oppilaille myös opettajille ja että ylhäältä alas suuntautuvat kehittämistoimet, kuten rehtorin sitoutuminen ja tuki sekä hallintokuntien kehittämistyö, voivat edistää käytännön oppilashuoltotyötä ja sen puitteita kouluissa. Tulokset korostavat aikuisten merkitystä lasten hyvinvoinnin kannalta: jos lasten elämää halutaan parantaa, on keskityttävä siihen mitä aikuiset tekevät. On myös tärkeää vahvistaa psykososiaalisen hyvinvoinnin merkitystä sekä tunne- ja ihmissuhdetaitojen itseisarvoa suomalaisessa koulussa. Yliopistoissa tulisi panostaa oppilashuollon ja koulupsykologityön tutkimukseen sekä kasvatuksen ja koulutuksen konteksteissa työskentelevien psykologien kouluttamiseen. Oman kouluhyvinvointiin keskittyvän tutkimuskeskuksen perustamista tulisi myös harkita.